2014
DOI: 10.1007/978-3-319-08894-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Potential of Astroglial Purinergic Receptors

Abstract: Acute brain injury and neurodegenerative disorders may result in astroglial activation. Astrocytes are able to determine the progression and outcome of these neuropathologies in a beneficial or detrimental way. Nucleotides, e.g. adenosine 5'-triphosphate (ATP), released after acute or chronic neuronal injury, are important mediators of glial activation and astrogliosis.Acute injury may cause significant changes in ATP balance, resulting in (1) a decline of intracellular ATP levels and (2) an increase in extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 250 publications
2
8
0
Order By: Relevance
“…It should also be noted that ATP-mediated P2Y 1 R activation is one of the key signals for the developing of reactive gliosis in several brain injury conditions (Franke and Illes, 2014 ; Shinozaki et al, 2017 ), which could explain the strong astrogliosis described previously in our epilepsy model as well as in others (Pernot et al, 2011 ; Morales et al, 2014 ; Buckmaster et al, 2017 ). Unlike previous reported findings (Di Castro et al, 2011 ), we observed that spontaneous astroglial somatic Ca 2+ signals do not require P2Y 1 R activation in the control condition, since their blockade has no effect on Ca 2+ oscillations (Figure 2 ).…”
Section: Discussionsupporting
confidence: 60%
“…It should also be noted that ATP-mediated P2Y 1 R activation is one of the key signals for the developing of reactive gliosis in several brain injury conditions (Franke and Illes, 2014 ; Shinozaki et al, 2017 ), which could explain the strong astrogliosis described previously in our epilepsy model as well as in others (Pernot et al, 2011 ; Morales et al, 2014 ; Buckmaster et al, 2017 ). Unlike previous reported findings (Di Castro et al, 2011 ), we observed that spontaneous astroglial somatic Ca 2+ signals do not require P2Y 1 R activation in the control condition, since their blockade has no effect on Ca 2+ oscillations (Figure 2 ).…”
Section: Discussionsupporting
confidence: 60%
“…Proliferation of reactive astrocytes termed astrogliosis is mediated not only by ATP acting at P2X7Rs, but also by additional nucleotide receptors of the P2X and P2Y types [36,37]. However, ATP is only one of the numerous endogenous factors determining astrogliosis, acting alone or together with cytokines (IL, TNF, or interferons), growth factors (FGF-2 or leukemia inhibitory factor), neurotransmitters (glutamate or noradrenaline), reactive oxygen radicals, nitric oxide, etc.…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory process or a hypoxic or traumatic brain insult could initially activate microglia, which release ATP and stimulate neighboring astrocytes through activating purinergic receptors, including P2Y (i.e., P2Y1) and P2X (i.e., P2X7) (Franke and Illes 2014; Pascual and others 2012). Activated astrocytes consequently release more ATP through Ca 2+ -dependent exocytotic and nonexocytotic processes, with the spread of Ca 2+ waves within the astrocyte network as the amplifying mechanism (Pascual and others 2012).…”
Section: Pharmacological Tools As Modulators Of Astroglial Ca2+-depenmentioning
confidence: 99%
“…The ATP released from astrocytes can enter the extracellular space, likely via connexin and pannexin hemichannels, which can be inhibited by 10PanX and GAP26 mimetic peptides (Shigetomi and others 2018; Wellmann and others 2018), and by Ca 2+ -dependent vesicular exocytosis. This pathway generates slow, long-lasting P2Y1-mediated astrocytic Ca 2+ transients that propagate on a large scale (Shigetomi and others 2018; Wellmann and others 2018), thereby inducing astrogliosis in the astrocyte network (Franke and Illes 2014; Shinozaki and others 2017). Reactive astrocytes subsequently overexpress P2Y1 receptors, which have been implicated in the generation of long-lasting astrocytic Ca 2+ transients in astrocytes (Alves and others 2017; Franke and Illes 2014; Pascual and others 2012; Shigetomi and others 2018).…”
Section: Pharmacological Tools As Modulators Of Astroglial Ca2+-depenmentioning
confidence: 99%
See 1 more Smart Citation